2002
DOI: 10.2190/2wnc-ec4r-3u45-pjr2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Problems in Christian and Moslem Primary Care Patients in Greece

Abstract: Mental health problems are common in primary care although they rarely constitute a reason for consultation. Sociocultural background may affect the presentation of psychological distress. Primary health care staff have a significant role in identifying hidden psychiatric morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 4 publications
3
6
0
Order By: Relevance
“…In this study, consistent with previous studies thirty two percent the people were detected as likely cases according to GHQ (22)(23)(24)(25). On the other hand, in a Bangladesh study, probably prevalence of mental disorders was found 19.7 percent.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, consistent with previous studies thirty two percent the people were detected as likely cases according to GHQ (22)(23)(24)(25). On the other hand, in a Bangladesh study, probably prevalence of mental disorders was found 19.7 percent.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with other reports showing a higher incidence of somatization within Muslim as compared with Christian communities (51)(52) and is in line with the fact that the female identity in Muslim communities is predominantly affected by their role in the family (53). Further studies are needed in order to elucidate the nature of how cultural variables, such as the role of women in the family, are associated with somatization among Muslim adolescents.…”
Section: Dysmenorrhea and Somatization In Arab Adolescentssupporting
confidence: 90%
“…An extensive literature review identified only three studies on religion and somatization. One found differences in somatic complaints across religious denominations (Androutsopoulou et al, 2002), and another found denominational differences in beliefs about the underlying causes of psychologically related somatic complaints (Chaturvedi and Bhandari, 1989). The last of the three studies found no significant relationship between somatization disorder and either organizational or private religious activities (Koenig et al, 1993a).…”
Section: Religion and Psychiatric Problemsmentioning
confidence: 97%